2018
DOI: 10.1101/309559
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic regulatory mechanisms of smooth muscle cells map to coronary artery disease risk loci

Abstract: Coronary artery disease (CAD) is the leading cause of death globally. Genome-wide association studies (GWAS) have identified more than 95 independent loci that influence CAD risk, most of which reside in non-coding regions of the genome. To interpret these loci, we generated transcriptome and whole-genome datasets using human coronary artery smooth muscle cells (HCASMC) from 52 unrelated donors, as well as epigenomic datasets using ATAC-seq on a subset of 8 donors. Through systematic comparison with publicly a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…We obtained primary HCASMC lines from commercial vendors. Genotypes were called with whole genome sequencing or genotyping with Illumina chips, phased and imputed against 1000 Genome phase 3 data before merging [14]. We pooled 65 lines for TCF21 ChIPseq and Hi-C, and 71 lines for ATACseq experiments at passage 4-6 ( Fig.…”
Section: Results Bqtl Caqtl and Clqtl Calling In Pooled Hcasmc Linesmentioning
confidence: 99%
See 4 more Smart Citations
“…We obtained primary HCASMC lines from commercial vendors. Genotypes were called with whole genome sequencing or genotyping with Illumina chips, phased and imputed against 1000 Genome phase 3 data before merging [14]. We pooled 65 lines for TCF21 ChIPseq and Hi-C, and 71 lines for ATACseq experiments at passage 4-6 ( Fig.…”
Section: Results Bqtl Caqtl and Clqtl Calling In Pooled Hcasmc Linesmentioning
confidence: 99%
“…QTLs of the CAD-associated transcription factor TCF21 were of particular interest because of the enrichment of its binding in other CAD loci [26] and contribution to the risk at these loci where it modulates the epigenome and thus expression of causal genes [15,27]. We have previously shown that CAD-associated variants are enriched in HCASMC regions of open chromatin [23], and that these cells contribute a significant portion of CAD risk [14]. There was at most 40% overlap of the HCASMC caQTLs with those reported previously for LCLs [9], suggesting that regulatory variation is quite different between these two cell types and underscoring the importance of these smooth muscle cell data for study of vascular disease genetics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations